Enhancing alginate dialdehyde-gelatin (ADA-GEL) based hydrogels for biofabrication by addition of phytotherapeutics and mesoporous bioactive glass nanoparticles (MBGNs) - Bider, Faina; Gunnella, Chiara; Reh, Jana; Clejanu, Corina Elena; Kuth, Sonja; Beltrán, Ana M.; Boccaccini, Aldo R. (Journal of Biomaterials Applications, 2024)
This study explores the 3D printing of alginate dialdehyde-gelatin (ADA-GEL) inks incorporating phytotherapeutic agents, such as ferulic acid (FA), and silicate mesoporous bioactive glass nanoparticles (MBGNs) at two different concentrations. 3D scaffolds with bioactive properties suitable for bone tissue engineering (TE) were obtained. The degradation and swelling behaviour of films and 3D printed scaffolds indicated an accelerated trend with increasing MBGN content, while FA appeared to stabilize the samples. Determination of the degree of crosslinking validated the increased stability of hydrogels due to the addition of FA and 0.1% (w/v) MBGNs. The incorporation of MBGNs not only improved the effective moduli and conferred bioactive properties through the formation of hydroxyapatite (HAp) on the surface of ADA-GEL-based samples but also enhanced VEGF-A expression of MC3T3-E1 cells. The beneficial impact of FA and low concentrations of MBGNs in ADA-GEL-based inks for 3D (bio)printing applications was corroborated through various printing experiments, resulting in higher printing resolution, as also confirmed by rheological measurements. Cytocompatibility investigations revealed enhanced MC3T3-E1 cell activity and viability. Furthermore, the presence of mineral phases, as confirmed by an in vitro biomineralization assay, and increased ALP activity after 21 days, attributed to the addition of FA and MBGNs, were demonstrated. Considering the acquired structural and biological properties, along with efficient drug delivery capability, enhanced biological activity, and improved 3D printability, the newly developed inks exhibit promising potential for biofabrication and bone TE.
CRIS-Team Scopus Importer:2024-10-04
Keywords: 3D (bio)printing; bioactive glass particles; bone tissue engineering; drug delivery; Hydrogels; phytotherapeutic agent